The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2024
DOI: 10.3390/jcm13041017
|View full text |Cite
|
Sign up to set email alerts
|

Current Insights and Novel Cardiovascular Magnetic Resonance-Based Techniques in the Prognosis of Non-Ischemic Dilated Cardiomyopathy

Francesco Perone,
Ilaria Dentamaro,
Lucia La Mura
et al.

Abstract: Cardiac magnetic resonance (CMR) imaging has an important emerging role in the evaluation and management of patients with cardiomyopathies, especially in patients with dilated cardiomyopathy (DCM). It allows a non-invasive characterization of myocardial tissue, thus assisting early diagnosis and precise phenotyping of the different cardiomyopathies, which is an essential step for early and individualized treatment of patients. Using imaging techniques such as late gadolinium enhancement (LGE), standard and adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…An indexed left ventricular end-diastolic volume (LVEDVi) on CMR > 120.5 mL/m2 and the presence of more than three segments with midwall fibrosis are independent predictors of all causes of death (Guaricci et al, 2021). Because of direct right ventricular involvement, Juillière et al found that right ventricular ejection fraction (RVEF) is a minor predictor of hospitalisation for heart failure (HF) in patients with DCM and an independent predictor of all-cause mortality (Perone et al, 2024). The left atrial volume index (LAVi), a sensitive indicator of LV filling pressure and a significant predictor of transplant-free survival and heart failure risk, is another parameter that might be assessed by CMR (Perone et al, 2024).…”
Section: Traditional Risk Stratification Approach In Dcmmentioning
confidence: 99%
“…An indexed left ventricular end-diastolic volume (LVEDVi) on CMR > 120.5 mL/m2 and the presence of more than three segments with midwall fibrosis are independent predictors of all causes of death (Guaricci et al, 2021). Because of direct right ventricular involvement, Juillière et al found that right ventricular ejection fraction (RVEF) is a minor predictor of hospitalisation for heart failure (HF) in patients with DCM and an independent predictor of all-cause mortality (Perone et al, 2024). The left atrial volume index (LAVi), a sensitive indicator of LV filling pressure and a significant predictor of transplant-free survival and heart failure risk, is another parameter that might be assessed by CMR (Perone et al, 2024).…”
Section: Traditional Risk Stratification Approach In Dcmmentioning
confidence: 99%